Fostering Livelihoods: Exploring the Scope and Challenges of Non-Timber Forest Products in Magar Community - Sapkota, Khila Nath (Economic Review of Nepal, 2021)
The paper aims to investigate the management practices and income-generating potential of non-timber forest products (NTFPs) in promoting the livelihoods of the Magar community in Janjang Village, Sindhuli. The Magar community, a marginalized indigenous nationality in Nepal, relies on NTFPs harvested from nearby forests. The study evaluates the commercial significance of NTFPs and the involvement of Magars in their trade, particularly with India. Through an empirical approach, the research involved unstructured interviews with fifteen local households to gather information. Findings indicate that while the collection and trade of NTFPs may not be a lucrative income source for individuals with higher landholdings, food security, and alternative income streams, it holds significant importance for Magars lacking access to land and alternative sources of income. It is a very nominal price offered for the NTFPs collected by the Magar community which does not even cover the labor costs (Piya et al., 2013). In response to the identified challenges, the community has recognized the need for collective action and established the Magar Community Support Cooperative Limited (MSCL) to facilitate and enhance NTFP trading. The cooperative has implemented institutionalized practices to streamline the processes involved in the collection, management, marketing, and trading of non-timber forest products (NTFPs). This cooperative structure aims to improve the overall efficiency and effectiveness of NTFP-related activities, fostering sustainable livelihoods for the Magar community in the Janjang Village of Sindhuli.